The contribution of ventilation on the energy performance of small residential buildings in the Mediterranean region - Fernandes, Marco S. (2020)
Efficient ventilation is an effective method for reducing thermal loads inside buildings, thus decreasing cooling energy consumption. This is especially relevant in warmer climates. Therefore, it is important to better understand the role that different ventilation parameters play on air-conditioning consumptions. This study analyzes the effect of three different ventilation parameters – air flow rate, minimum indoor temperature and indoor-outdoor temperature difference – on the energy performance of buildings in the Mediterranean region. A set of 500 residential building geometries was randomly generated and the energy consumption for different combinations of ventilation parameters was assessed in sixteen distinct locations. Results suggested that the ventilation specifications that minimize air-conditioning energy consumption fall within similar values for all the evaluated locations: ventilation rates of at least 10 air changes per hour, a minimum indoor temperature for ventilation slightly below the building’s cooling setpoint, and a low indoor-to-outdoor temperature difference. It was also found that, in lower latitudes, the buildings’ energy performance tended to become similar, thus reducing the impact of their geometry and orientation. These results may help building practitioners to infer the most adequate ventilation strategies to implement, since this study is not limited to specific ventilation methods.